1979
DOI: 10.3354/meps001055
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Particle Retention and Filtration Rate in Four Species of Ascidians

Abstract: Particle retention in Ascidiella aspersa, Molgula manhattensis, Clavelina lepadiformis and Ciona intestinalis was determined from comparisons of particle-size distributions in the inhaled and exhaled water. Particles down to 2-3 jun were completely retained and the retention efficiency of smaller particles decreased to about 70 "/o for 1 ~u n particles. There was no indication that the ascidians were able to adjust their retention efficiency. Filtration rates (F, m1 min-l) as a function of total dry weight (W,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(49 citation statements)
references
References 12 publications
5
44
0
Order By: Relevance
“…The gorgonian Paramuricea clavata fed predominantly on detritus and zooplankton. These results are consistent with the size spectrum of efficient filtration reported for sponges and ascidians (Randøv & Riisgård 1979, Jørgensen et al 1984, Ribes et al 1998a, 1999a. The retention spectrum of passive filter feeding in gorgonians ranges from 3.8 µm (nanoeukaryotes) to large seston particles several hundred microns in diameter, such as detrital particles and zooplankton (Coma et al 1994, Ribes et al 1998b, 1999b.…”
Section: Resale or Republication Not Permitted Without Written Consensupporting
confidence: 85%
“…The gorgonian Paramuricea clavata fed predominantly on detritus and zooplankton. These results are consistent with the size spectrum of efficient filtration reported for sponges and ascidians (Randøv & Riisgård 1979, Jørgensen et al 1984, Ribes et al 1998a, 1999a. The retention spectrum of passive filter feeding in gorgonians ranges from 3.8 µm (nanoeukaryotes) to large seston particles several hundred microns in diameter, such as detrital particles and zooplankton (Coma et al 1994, Ribes et al 1998b, 1999b.…”
Section: Resale or Republication Not Permitted Without Written Consensupporting
confidence: 85%
“…Cilia on the papillae or longitudinal pharyngeal bars transport the endless mucus net, with the retained food particles, to the dorsal side where it is rolled into a cord which is passed downwards into the oesophagus as an Riisgård et al (1992) continuous string (MacGinitie 1939, Millar 1971, FialaMédioni 1978. Particles down to 2 or 3 µm are completely retained (Randløv & Riisgård 1979, Jørgensen et al 1984, and electron microscope studies of the mucus net have revealed that in the fixed state, it is composed of 10 to 40 nm thick fibres arranged in rectangular meshes that vary between 0.2 and 0.5 µm in width and between 0.5 and 2.2 µm in length (Fig. 13B,C) (Flood & Fiala-Médioni 1981).…”
Section: Tunicatesmentioning
confidence: 99%
“…Much of their morphology can be linked to functions related to active suspension feeding, which has been studied extensively in adult ascidians and bivalves (e.g. FialaMedioni 1978, Flood & Fiala-Medioni 1979, Randløv & Riisgård 1979, Jørgensen et al 1984, Riisgård 1988, Petersen & Riisgård 1992, Riisgård & Larsen 1995, Kowalke 1999, Petersen & Svane 2002. The physical mechanisms of flow generation during active suspension feeding are well understood, and the effects of morphology and size on feeding performance are readily quantifiable (Rubinstein & Koehl 1977, Jør-gensen et al 1984, LaBarbera 1984, Riisgård 1988.…”
Section: Introductionmentioning
confidence: 99%
“…1). Food particles are captured with high retention efficiency (Randløv & Riisgård 1979) on a mucous net inside the basket and, together with the net, are passed into the stomach. We will focus here on the effects of siphon and basket morphology on the resistance to flow, pump power and the region of water sampled.…”
Section: Introductionmentioning
confidence: 99%